2019
DOI: 10.5553/benm/138900692019046003004
|View full text |Cite
|
Sign up to set email alerts
|

Sociale cohesie in gentrificerende arbeiderswijken van Amsterdam-Noord

Abstract: De krapte in het Amsterdamse woningaanbod en de bijbehorende stijgende huuren huizenprijzen geven steeds meer mensen reden tot zorg over het inclusieve karakter van de stad (Milikowski, 2018). Biedt de stad vooral ruimte aan groepen die al kansrijk zijn, en steeds minder aan kansarmen? En wat doet de toename van welvarendere bewoners met de sociale cohesie van zogenoemde kwetsbare wijken? 1 Voelen mensen zich nog wel thuis in hun buurt? De economische en culturele opwaardering van kwetsbare stadswijken door de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…They also indicated that the activities organized by "the yuppies," such as yoga and mindfulness, were fine as long as "we don't need to participate." As long as they have the possibility to meet and organize their own activities, such as bingo and dance evenings, and can drink coffee that costs one euro, these residents feel they still belong in the neighborhood (L. van de Kamp & Welschen, 2019). For the long-term, low-income residents who live on social security, the close-knit relationships they have with each other are crucial for them "to get by" (de Souza Briggs, 1998).…”
Section: Social Practices: the Church As A Socially Mixed Community C...mentioning
confidence: 99%
See 1 more Smart Citation
“…They also indicated that the activities organized by "the yuppies," such as yoga and mindfulness, were fine as long as "we don't need to participate." As long as they have the possibility to meet and organize their own activities, such as bingo and dance evenings, and can drink coffee that costs one euro, these residents feel they still belong in the neighborhood (L. van de Kamp & Welschen, 2019). For the long-term, low-income residents who live on social security, the close-knit relationships they have with each other are crucial for them "to get by" (de Souza Briggs, 1998).…”
Section: Social Practices: the Church As A Socially Mixed Community C...mentioning
confidence: 99%
“…12 They also said that the Church’s community center offered coffee and tea for a “normal price” 13 or free of charge. The residents commented and exclaimed that “these new places in the neighborhood serve coffee for four euro!” They also indicated that the activities organized by “the yuppies,” such as yoga and mindfulness, were fine as long as “we don’t need to participate.” As long as they have the possibility to meet and organize their own activities, such as bingo and dance evenings, and can drink coffee that costs one euro, these residents feel they still belong in the neighborhood (L. van de Kamp & Welschen, 2019).…”
Section: Social Practices: the Church As A Socially Mixed Community C...mentioning
confidence: 99%